Generation of Mouse Bone Marrow-Derived Macrophages (BM-MFs) - Ivan Zanoni; Renato Ostuni; Francesca Granucci (Bio-Protocol, 2012)
Generating mouse macrophages from bone-marrow progenitor cells is a useful tool to study biological functions of mouse macrophages. Macrophages are one of the major populations of phagocytes and play many different roles during inflammatory process initiation and termination.